STRATEGY TO INCREASE THE CLASS OF FARMER GROUPS IN BERMANI ILIR DISTRICT, KEPAHIANG REGENCY - Nikofien, Mhareuzi; Yuliarso, M. Zulkarnain; Priyono, Basuki Sigit (Journal of Agri Socio Economics and Business, 2025)
The strategy of upgrading the class of farmer groups can include various components, such as member skill development, increasing agricultural production, effective financial management, marketing of crops, and risk management with the aim of improving the welfare and independence of farmer groups. Thus, farmer groups will be more productive and competitive in marketing their crops and carrying out their agricultural activities in a sustainable manner. Bermani Ilir District, Kepahiang Regency has a farmer group with the status of a beginner class as a whole, thus there is a need for a strategy to improve the class. This study was conducted in Bermani Ilir District with 9 expert respondents, 57 farmer group administrators and 57 farmer group members who were analyzed using SWOT. Based on the results obtained, the strategy for increasing the group class is in the WO strategy, namely by taking advantage of opportunities to minimize weaknesses. The results of the priority strategy obtained using QSPM analysis are that it was found that Improving Training and Administrative Management to Utilize Fertilizer Subsidies, infrastructure and land protection policies are strategies with the first priority as a strategy to increase the class of farmer groups in Bermani Ilir District, Kepahiang Regency.